2011
DOI: 10.2320/matertrans.l-mz201123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microalloying Tin and Combined Addition of Silver and Tin on the Formation of Precipitate Free Zones and Mechanical Properties in Al-Zn-Mg Alloys

Abstract: The additions of microalloying tin and (silver and tin)-combination were performed to modify the precipitate microstructure in the vicinity of grain boundaries with precipitate free zones (PFZs) and mechanical properties in Al-Zn-Mg alloys. In the Sn-containing alloy, TEM observation showed that some precipitates were sparsely formed within the region of PFZs of the Al-Zn-Mg ternary alloy. The quantitative analysis of the chemical compositions in precipitates showed that tin mainly contributes to nucleation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…The reason standing behind disappearance of some of the compounds in the MgZn phase through adding 0.5 wt.% Sn into the alloy A is attributed to the impacts of tin (Sn) in the nucleation within the vicinity of the grain boundaries which is resulting in the suppression of some of the sites, the creation for the MgZn phases within the matrix alloy B in this study present. This justification conforms with prior researchers: Ogura et al [23] observed that adding tin element into Al-Zn-Mg alloy led to precipitates suppression of the MgZn phases which are sparsely formed within the microstructure. The outcomes of XRD analysis of alloy B conform to the EDS scan results as noticed in Figure 10(b).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The reason standing behind disappearance of some of the compounds in the MgZn phase through adding 0.5 wt.% Sn into the alloy A is attributed to the impacts of tin (Sn) in the nucleation within the vicinity of the grain boundaries which is resulting in the suppression of some of the sites, the creation for the MgZn phases within the matrix alloy B in this study present. This justification conforms with prior researchers: Ogura et al [23] observed that adding tin element into Al-Zn-Mg alloy led to precipitates suppression of the MgZn phases which are sparsely formed within the microstructure. The outcomes of XRD analysis of alloy B conform to the EDS scan results as noticed in Figure 10(b).…”
Section: Resultssupporting
confidence: 91%
“…The intensity of the diffraction peaks Al 4 Ni 15 Sn and other peaked high such as Al 7 Cu 4 Ni, Al 4 Ni 3 , Al 75 Ni 10 Fe 15 and Al 3 Cu 12 Sn phases with a little coexistence of the Mg 2 Zn 11 phase.The reason standing behind disappearance of some of the compounds in the MgZn phase through adding 0.5 wt.% Sn into the alloy A is attributed to the impacts of tin (Sn) in the nucleation within the vicinity of the grain boundaries which is resulting in the suppression of some of the sites, the creation for the MgZn phases within the matrix alloy B in this study present. This justification conforms with prior researchers: Ogura et al[23] observed that adding tin element into Al-Zn-Mg alloy led to precipitates suppression of the MgZn phases which are sparsely formed within the microstructure. The outcomes of XRD analysis of alloy B conform to the EDS scan results as noticed in Figure10(b).After applying the aging at T6 temper and RRA process for the alloy A and alloy B, the yield maximum gains of about 385 and 415 MPa and 370 and 385 MPa were attained in the ultimate tensile strength (UTS), respectively.…”
supporting
confidence: 91%
“…It has been shown that the width of the PFZ adversely affects the fatigue crack growth behavior in aluminum alloys . The weaker PFZ surrounding the GBPs leads to the void formation during loading, which further coalesces and promotes intergranular cracking resulting in higher FCGRs .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the influence of grain refinement and grain growth on the FCGR behavior in RRA is expected to be negligible, a similar observation made by Xia et al 30 It has been shown that the width of the PFZ adversely affects the fatigue crack growth behavior in aluminum alloys. 47,48 The weaker PFZ surrounding the GBPs leads to the void formation during loading, which further coalesces and promotes intergranular cracking resulting in higher FCGRs. 23 In the present study, the RRA treatment resulted in marginal increment of PFZ width compared with the T6-treated alloy (Figure 2B,D).…”
Section: Effect Of the Rra On The Fatigue Crack Propagation Behaviormentioning
confidence: 99%
“…The longer the transfer time is, the more disappeared vacancy in the grain boundary is. During aging, GP zone cannot appear in the area that is lower than the critical vacancy concentration, and thus a precipitationfree zone forms [15,16]. So, if the transfer time is extended, the width of the precipitation-free zone becomes significant, and the mechanical properties and conductivity of alloy are deteriorated.…”
Section: Influence Of Transfer Time Before Quenching On Mechanical Prmentioning
confidence: 99%